PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TAKE AND GIVE UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS VA SDN 42 PEKANBARU - Kurnia, Putri; Alpusari, Mahmud; Lazim N, Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research was conducted because of the result of learning science studies of grade VA SDN 42 Pekanbaru, with a class average of 57,94 minimum clompleteness criteria achieved by school was 75. From 39 students who achieve minimum clompleteness criteria just 5 students (12.82%) while students who did’nt achieve minimum clompleteness criteria is 34 students (87.18%). The purpose of this research to improve learning achievement science of grade VA students of SDN 42 Pekanbaru with the implementation of cooperative learning model type Take and Give. The results obtained by the average value of 57.94 firts score increased in the first cycle of 39,48% to 80.82. In the second cycle the average value of students also increased by 43.37% to 83.07. On the basic of classical completeness score science studies learning outcomes is only 12,82% (not finished). After the professor of applied cooperative learning model type of Take and Give in the first cycle classical completeness increased to 76,92% (not finished), and the second cycle of classical completeness obtained are increased to increase to 92,30%. Activities of teachers at the first learning of first cycle acquire a percentage of 79.17% with good categories. The second learning increased to 83.35% in good category. In the first learning of second cycle increased to 87.50% with very good category. At the second learning increased to 91.67% with very good category. At the third learning increased to 95.83% with good category. Activities of students in the first learning of the first cycle acquire a percentage of 62.50% with enough category. The second learning increased to 70.83% in enough category. In the first learning of the second cycle increased to 79.17% with good category. At the second learning increased to 83.33% with good category. At the third learning increased to 91.67% with very good category. The conclusion of this research was the implementation of cooperative learning model type Take and Give can improve student’s achievement science studies of grade VA SDN 42 pekanbaruKeywords: Take and Give, Science Studies Learning